Comparison of the effects of nursing and peer education on quality of life and resilience in patients with multiple sclerosis: A randomized clinical trial - Mohammad Mehdi Siahvashi; Morteza Shamsizadeh; Leli Tapak; Masoud Ghiasian; Azim Azizi (Heliyon, 2024)
Background: Multiple sclerosis (MS) is a prevalent disease of the central nervous system that often leads to diminished resilience and quality of life in affected individuals. This study aims to compare the effects of nursing and peer education on improving the quality of life and resilience in patients with multiple sclerosis. Materials and methods: This three-group clinical trial study was conducted before and after interventions at the MS Society in Hamedan, Iran. In this study, 120 patients with MS were randomly selected and assigned to three groups: nurse education, peer education, and control. Quality of life and resilience questionnaires were self-reported before and two months after the completion of the intervention. The educational sessions were conducted over five meetings, each lasting between 45 and 60 min, held every two days. Group one received education led by nurses, while group two participated in peer-led education sessions. Results: The results indicated that before the intervention, there were no significant statistical differences in demographic variables, resilience, and quality of life among the three groups (p > 0.05). However, after the intervention, both the peer and nurse groups showed a significant increase in quality of life and resilience compared to the control group (p < 0.05). Nevertheless, no differences were observed between the nurse and peer groups regarding these variables (p > 0.05). Conclusions: Both nursing and peer education methods had an equal impact on enhancing the resilience and quality of life of patients with MS. It is recommended that peer support be utilized to empower MS patients, especially in contexts where there is a shortage of nurses.